Follow-up care of 12 months of patients with bladder cancer in Spain: A multicenter prospective cohort study. Issue 42 (21st October 2022) - Bonfill, Xavier; Martinez-Zapata, María José; Barrionuevo-Rosas, Leslie; Vernooij, Robin WM; Sánchez, María José; Morales-Suárez-Varela, María; De la Cruz, Javier; Emparanza, José Ignacio; Ferrer, Montserrat; Pijoan, José Ignacio; Palou, Joan; Frances, Albert; et al.
Abstract : The therapeutic approach of bladder cancer strongly determines its prognosis. We describe the treatments and outcomes for a Spanish cohort of patients with bladder cancer for the first 12 months after diagnosis and identify the factors that influenced the decision to undergo the treatment received. We conducted a multicenter, prospective, cohort study including primary bladder cancer patients during the first 12 months after diagnosis. The clinical outcomes were performance status (ECOG), adverse events and any cause of mortality. We stratified the analysis by factors that might influence the treatments received. We conducted univariate and multivariable logistic regression models to assess which patient and tumor characteristics were associated with receiving adjuvant treatment in the subgroup of noninvasive bladder cancer patients. In total, 314 patients were included (85% men; 53.8% >70 years) in 7 tertiary Spanish hospitals; 82.2% had a noninvasive urothelial bladder cancer (NMIBC). Patients received mostly surgery plus adjuvant therapy (67.7%). BCG (32.8% patients) was the most frequently administered adjuvant therapy, followed by intravesical chemotherapy (17.8% patients) and radiotherapy (10.8%). The variability of administered treatments among hospitals was low. Patients with NMIBC were more likely to receive adjuvant therapy if they had a higher educational level, some comorbidities and a high-grade tumor. The number of fully active patients (ECOG 0) significantly decreased during the first year of follow-up from 58% to 36 % (OR: 2.41, 95%CI 1.82–3.20); at 12-month follow-up 10.8% patients had died from any cause. In conclusion, most of the patients had a NMIBC. Surgery alone or plus adjuvant therapy were the commonest curative options of bladder cancer. BCG therapy was the adjuvant therapy most frequently administered. Higher educational level, presence of comorbidities and a high-grade tumor were associated with adjuvant therapy. Patient performance status was worsening over time. Almost 1 of 10 patients died during the first year of follow-up.